Kinase‐Catalyzed Crosslinking and Immunoprecipitation (K‐CLIP) to Explore Kinase‐Substrate Pairs. Issue 9 (22nd September 2022) - Beltman, Rachel J.; Pflum, Mary Kay H.
Abstract: Kinases are responsible for phosphorylation of proteins and are involved in many biological processes, including cell signaling. Identifying the kinases that phosphorylate specific phosphoproteins is critical to augment the current understanding of cellular events. Herein, we report a general protocol to study the kinases of a target substrate phosphoprotein using kinase‐catalyzed crosslinking and immunoprecipitation (K‐CLIP). K‐CLIP uses a photocrosslinking γ‐phosphoryl‐modified ATP analog, such as ATP‐arylazide, to covalently crosslink substrates to kinases with UV irradiation. Crosslinked kinase‐substrate complexes can then be enriched by immunoprecipitating the target substrate phosphoprotein, with bound kinase(s) identified using Western blot or mass spectrometry analysis. K‐CLIP is an adaptable chemical tool to investigate and discover kinase‐substrate pairs, which will promote characterization of complex phosphorylation‐mediated cell biology. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Kinase‐catalyzed crosslinking of lysates Basic Protocol 2 : Kinase‐catalyzed crosslinking and immunoprecipitation (K‐CLIP)